(untitled) (IJM: Journal of Multidisiplinary, 2025)
This study examines the effect of work motivation and work environment on employee performance in a company. Employee performance plays a crucial role in the company's success, although some employees have not demonstrated optimal performance. The purpose of this study is to identify the impact of work motivation and work environment on employee performance. The study uses a population of 32 respondents and adopts an explanatory research design, collecting both qualitative and quantitative data, including primary and secondary data. Data analysis was conducted using SPSS version 26. The results indicate that approximately 70.4% of employee benefits are influenced by the variables of work motivation and work environment. Therefore, companies need to continually enhance work motivation and the work environment to ensure employees' performance remains optimal. It is important for companies to provide daily training and keep employees motivated. Further research is needed to explore other factors affecting employee performance.